2016
DOI: 10.1007/s11356-016-7970-9
|View full text |Cite
|
Sign up to set email alerts
|

Metals as chemical tracers to discriminate ecological populations of threatened Franciscana dolphins (Pontoporia blainvillei) from Argentina

Abstract: Franciscana dolphins are the most impacted small cetacean in the Southwestern Atlantic Ocean, classified as Vulnerable A3d by IUCN. Essential (Fe, Mo, Mn, Cr, Ni, Co) and non-essential (Ag, Pb, Sn) trace elements (TEs) were measured in liver, kidney, and brain samples of by-catch Franciscana dolphins that were living in estuarine (n = 21) and marine (n = 21) habitats (1) to assess whether TEs posed a threat and (2) to evaluate the suitability of TEs for discriminating ecological populations of this species in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 77 publications
1
3
0
Order By: Relevance
“…With regard to trace elements, Seixas et al (2008) found that the concentrations of selenium (Se), total mercury (Hg), and organic mercury (OrgHg) were higher in the livers and kidneys of franciscanas from Rio Grande do Sul State than Rio de Janeiro State, Brazil. For both areas, the values were of the same order of magnitude as those reported in earlier studies with the same species from Brazil (Lailson-Brito et al, 2002;Kunito et al, 2004;Seixas et al, 2007) and Argentina (Marcovecchio et al, 1994;Gerpe et al, 2002;Denuncio et al, 2017;Romero et al, 2017). Franciscana livers showed higher concentrations of mercury, zinc, and copper relative to concentrations in other organs, whereas their highest cadmium concentrations were mostly found in kidneys (Marcovecchio et al, 1990;Gerpe et al, 2002;Lailson-Brito et al, 2002;Kajiwara et al, 2004;Seixas et al, 2008).…”
Section: Chemical Pollutionsupporting
confidence: 83%
“…With regard to trace elements, Seixas et al (2008) found that the concentrations of selenium (Se), total mercury (Hg), and organic mercury (OrgHg) were higher in the livers and kidneys of franciscanas from Rio Grande do Sul State than Rio de Janeiro State, Brazil. For both areas, the values were of the same order of magnitude as those reported in earlier studies with the same species from Brazil (Lailson-Brito et al, 2002;Kunito et al, 2004;Seixas et al, 2007) and Argentina (Marcovecchio et al, 1994;Gerpe et al, 2002;Denuncio et al, 2017;Romero et al, 2017). Franciscana livers showed higher concentrations of mercury, zinc, and copper relative to concentrations in other organs, whereas their highest cadmium concentrations were mostly found in kidneys (Marcovecchio et al, 1990;Gerpe et al, 2002;Lailson-Brito et al, 2002;Kajiwara et al, 2004;Seixas et al, 2008).…”
Section: Chemical Pollutionsupporting
confidence: 83%
“…6c). The median Pb values from the firing range was highest compared to some wild terrestrial (Kalisinska et al, 2016) and marine (Cardellicchio et al, 2002;Romero et al, 2017) mammals. Lead concentrations in all the brain samples from the Ukumehame firing range and two of the eight from Hilo Airport exceeded the mean Pb level observed in the brain of male rats (0.239 µg g −1 WW), which were exposed to 50 mg/L Pb and had increased ambulatory activity measured as lines crossed (Mansouri et al, 2012).…”
Section: Discussionmentioning
confidence: 88%
“…This protective effect could be because essential metals (e.g., Zn) are inducers of the synthesis of metallothioneins (MTs), which are involved in metal detoxification [ 17 ]. The metal concentrations in cetaceans are mainly estimated in the kidney and liver because these organs are, respectively, involved in immune response, biotransformation of toxic compounds, and renal filtration; however, some studies are also focused on metal levels in muscle [ 7 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Unfortunately, it is not possible to compare the metal contaminations determined in distinct cetacean species, because they were collected in different geographical zones and years.…”
Section: Introductionmentioning
confidence: 99%